HUBUNGAN HEALTH BELIEF TERHADAP KEPATUHAN PENGOBATAN LANSIA PENDERITA HIPERTENSI - Icca Narayani Pramudaningsih Icca (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
The elderly are an age group that has reached the final stage of life. The increase in the elderly population cannot be separated from health problems in the elderly, a decrease in organ function causes the emergence of various kinds of degenerative diseases. Degenerative diseases that many elderly suffer from include hypertension, cataracts, stroke, Diabetes mellitus, joint disorders, mental and heart disorders (RISKESDAS, 2018). Based on the results of Basic Health Research (Riskesdas) in 2018, the prevalence of hypertension in Indonesia in the population aged â‰¥18 years was 34.11%. One of the causes of the high prevalence of hypertension is the reduced control rate for hypertension sufferers. This is shown in the results of a survey from the Ministry of Health in 2019, as many as 32.3% of hypertension sufferers do not regularly take hypertension medication and 13.3%. The impact of non-compliance with treatment is a significant and multiple decline in health status. The aim of this research is to determine the relationship between health beliefs and treatment compliance in elderly people with hypertension. The design of this research is quantitative destructive research with a cross sectional approach. The data collection technique used was purposive sampling with a total sample of 60 respondents. The results of this study show a relationship between health beliefs and treatment compliance in elderly people with hypertension (p value = 0.032). Health service facilities are expected to be able to improve interventions in the education of line patients with hypertension, especially for elderly patients with hypertension who have poor health beliefs, so as to increase better perceptions of compliance with hypertension treatment.